Description of the immature stages of Trichocorixa mendozana Jaczewski (Hemiptera: Heteroptera: Corixidae) - Konopko, Susana Amanda; Mazzucconi, Silvia Ana; Bachmann, Axel Oscar (Zootaxa, 2011)
The egg and the instars I, IV, and V of Trichocorixa mendozana are described and illustrated for the first time. The eggs of Trichocorixa have a very short basal stalk; those of T. mendozana are bigger than those of T. kanza and T. sexcincta. The main characters separating the instars I, IV, and V of T. mendozana are: the head width; the number of transverse sulcations of the rostrum; the number of spines on the anterior surface of the metafemur; and the grade of development of the wing pads. The nymphs of T. mendozana and T. verticalis sellaris can be separated on the basis of the head (instar V) and body (instars I, IV–V) widths. In nymphs V of T. mendozana, T. orinocoensis, T. reticulata reticulata, T. verticalis sellaris, and T. verticalis verticalis, the following measurements and ratios distinguish species or group of species of Trichocorixa: the body length; the ocular index; the ratio between the body length and the head width; the ratio between the distance and the diameter of the apertures of the second and third scent glands; and the number of spines on the anterior surface of metafemur.